A plataforma de produção textual como tecnologia de ensino e o ensino de escrita em língua portuguesa na educação básica : a coconstrução textual da referência - Gonçalves, Rafaela (2017)
In this work, we approach, from Émile Benveniste's theorizations on written enunciation, the textual co-construction of the reference in compositions produced by users of the Uol Education Platform. We show, through descriptive and interpretive analysis, how these texts and their respective corrections are related to the current teaching of writing in Portuguese Language from the textual production in basic education, carried out by the formal institutions of education. In order to do so, it was also important for us to explain how the current teaching of writing from textual production is being based on entrance exams in higher education, especially Enem, and what this implies. Thus, because the speaker-writer needs to handle the written language due to their writing correfer to the other (the reader-evaluator), the concepts of appropriation of the written language and handling of the written language were re-significated from the concepts related to the spoken enunciation. The considerations of Émile Benveniste (2014 [1968 and 1969]) on the distinction between writing and written language; written language being understood as the language in its written form and writing an enunciative act which requires of the speaker-writer the appropriation of the written language and its use for a specific purpose, so that the speaker-writer is subjectivized by written in order to produce meanings. The affiliation to the thought of Émile Benveniste was relevant so that we could discuss an association between writing and copying, besides explaining the question of the influence of orality in the textual co-construction of the references present in the texts analyzed. Beforehand, we suggest the hypothesis that problems in the handling of linguistic forms would have some impact on the process of textual co-construction of the reference. From this, we question the importance of the teacher so that the teaching of writing is based on the students’ improvement to an institutionalized and subjective writing, in which the internal language is planned in consonance with the coercion of the written language necessary for the production of the docking effect, the co-referencing. Regarding the analytical procedures used to carry out this research, we divided the process into two parts. A first one, in which we analyze and quantify each text that composes our corpus of writing in order to find the problems of textual construction of the reference, which implied an opening of senses; and a second one, in which we analyze four (4) texts and the correction made by the Uol Education Platform for these productions. Based on our perception of the issues found in our reading-interpretation movement, we were able to question the role to which the teacher is subordinated in the current configurations of basic education, as well as the influence of entrance exams in higher education as the (only) purpose for teaching writing from textual production.